BRIDGING WESTERN LEARNING THEORIES AND ISLAMIC EDUCATIONAL PHILOSOPHY: A PHENOMENOLOGICAL INQUIRY INTO KURIKULUM BERBASIS CINTA - Fathurohim; Muhamad Habib; Ahmad Maliki; Imam Tobroni (Program Studi Manajemen Pendidikan Islam, 2026)
Contemporary educational discourse often faces a dichotomy between rigid behavioral measurement and fluid humanistic development, frequently neglecting the spiritual-emotional essence in Islamic contexts. This study explores the philosophical and practical integration of Behaviorism, Constructivism, and Humanism within the framework of a